Collaborative distance: investigating issues related to distance factors affecting collaboration performance - Pallot, Marc A. (2011)
Both organisations and individuals are using more collaborative work, across geographic, disciplinary and organisational boundaries, leading to increased demand for Information and Communication Technologies (ICT) to support a more effective and efficient distributed collaboration. This thesis presents an empirical study exploring various aspects related to collaborative distance in the context of innovation projects. It focuses on the investigation of issues related to distance factors that affect collaboration effectiveness and efficiency. A total of 14 focus group interviews, undertaken with 75 participants in a comparative study of 14 project cases, revealed sufficient evidence on distance factors in the context of mixed (face-to-face and online or virtual) collocation modes. The results confirmed the positive role of collaboration technology for compressing geographical and temporal types of distance; other distance types were also bridged, however, other distance types were created.